Indigenous archival activism: Mohican interventions in public history and memory - Miron, rose (Minneapolis University of Minnerrsota press, 2024)
Tracing one tribe's fifty-year fight to recover and rewrite its history, Indigenous Archival Activism takes readers into the heart of debates over who owns and has the right to tell Native American history and stories. Rose Miron tells the story of the Stockbridge-Munsee Mohican Nation and its Historical Committee, showing how their work is exemplary of how tribal archives can strategically shift how Native history is accessed, represented, written, and, most important, controlled.
Keywords: Ethnic Studies; History 20th Century; American Studies